The big five in the world of plants – the species that have changed the course of history - Święcick, Wojciech K; Surma, Maria (Polish Journal of Agronomy, 2021)
Following the big five of plant families presented by Hammer et al. (2015) an attempt was undertaken to select the big five of crop plants and genes. A large number of species (7 thousand of crops among 250 thousand of higher plants) as well as accepted criteria cause difficulties. Three cereals (wheat, rice, corn), potatoes (source of carbohydrates plus an influence on a history of three states) and soybean (main source of protein in animal feeds) were counted as plants having the greatest im- portance in human nutrition. Considered were also the genes, to a great extent influenced the productivity and use of those crops, making easier cropping and harvesting (genes Rht and Glu in wheat, Sd1 in rice, resistance to herbicide in soyabean), improv- ing grain quality (Glu and Gli in wheat and genes for beta caro- tene synthesis in rice) as well as resistance to pests (Bt in corn) and diseases (R in potatoes). Five species were also presented which played an outstanding role in nations, states or even con- tinents history (cinchona, sugar cane, tee bush, cotton, cocaine bush). According to the authors’ opinion as well as that of Hob- house’s (2005), Molenda’s (2011), and Laws’ (2016) these plants changed the course of the world’s history.